2020
DOI: 10.1186/s12936-020-03198-5
|View full text |Cite
|
Sign up to set email alerts
|

“We have this, with my husband, we live in harmony”: exploring the gendered decision-making matrix for malaria prevention and treatment in Nampula Province, Mozambique

Abstract: Background: Conceptualizing gender dynamics and ways of bridging entrenched gender roles will contribute to better health promotion, policy and planning. Such processes are explored in relation to malaria in Mozambique. Methods: A multi-method, qualitative study using focus group discussions (FGDs) and in-depth interviews (IDIs) explored the perspectives of community members, leaders and stakeholders on malaria. The study was conducted in Nampula Province, in an intervention district for the Tchova Tchova Stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Worship places (churches and mosques) are where respondents heard malaria preventive messages, and community dialogue sessions helped them better understand how to prevent malaria. Similarly, in a study conducted in Nampula Province, Mozambique, respondents affirmed that community dialogues helped communication and ultimately encouraged malaria-related behaviour [ 24 ]. These results indicate that the people implementing SBC interventions in Mozambique aid in dissemination of information and are accepted interlocutors by the beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…Worship places (churches and mosques) are where respondents heard malaria preventive messages, and community dialogue sessions helped them better understand how to prevent malaria. Similarly, in a study conducted in Nampula Province, Mozambique, respondents affirmed that community dialogues helped communication and ultimately encouraged malaria-related behaviour [ 24 ]. These results indicate that the people implementing SBC interventions in Mozambique aid in dissemination of information and are accepted interlocutors by the beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…Worship places (churches and mosques) are where respondents heard malaria preventive messages, and community dialogue sessions helped them better understand how to prevent malaria. Similarly, in a study conducted in Nampula Province, Mozambique, respondents a rmed that community dialogues helped communication and ultimately encouraged malaria-related behaviors [23]. These results indicate that the people implementing SBC interventions in Mozambique aid in the dissemination of the information and are accepted interlocutors by the bene ciaries.…”
Section: Discussionmentioning
confidence: 82%
“…Likewise, studies conducted among community members have found low levels of knowledge of malaria treatment [ 42 ]. Although the wider community (men and older women inclusive) may not have been optimally engaged on IPTp in the past, they have been found to play key roles in promoting interventions aimed at reducing malaria in pregnancy [ 43 ]. Thus, it is important that community engagement and knowledge translation is integrated into programs to control and/or eliminate malaria in pregnancy.…”
Section: Discussionmentioning
confidence: 99%